Effect of methacrylic acid and pendant vinyl groups on the mechanical properties of highly stretchable core–shell nanostructured films deposited from water. Issue 3 (17th December 2020) - Turton, James; Worrall, Stephen; Musa, Muhamad S.; Milani, Amir H.; Yao, Yichao; Shaw, Peter; Ring, David; Saunders, Brian R.
Abstract : The mechanical properties of these highly stretchable, water deposited elastomers can be tuned by varying MAA content and vinyl functionalisation. Abstract : With the continued drive to develop elastomers, improved methods are required to decrease the environmental impact of their preparation. Previously, such systems used Zn-based salts to form nanostructured ionomeric elastomers which had high modulus values, but only limited stretchability. Here, we investigate highly stretchable, additive-free, nanostructured films that are formed simply by casting aqueous core–shell nanoparticle dispersions and drying. The nanoparticles have a poly( n -butylacrylate) (PBA) core and the shell contains a crosslinked copolymer of BA, acrylonitrile (AN), methacrylic acid (MAA) and 1, 4-butanediol diacrylate (BDDA). The nanostructured films are shown to be highly stretchable (up to 1300%) and their toughness increases linearly with MAA content. The latter is due to hydrogen-bonding between the –COOH groups and AN. The core–shell nanoparticles are subsequently functionalised using glycidyl methacrylate (GMA) and the films heated to provide additional covalent crosslinking. We show that the vinyl group content can be evaluated using Raman spectroscopy. The latter also enables the monitoring of nanoparticle functionalisation by the reaction with GMA. Radical coupling of the vinyl groups upon heating of the films is shown to increase both the modulus and toughness of the films. Our new nanostructured films provide an alternative, additive-free, environmentally friendly approach for the preparation of highly stretchable water-based elastomers.